Characterization of the vibrations and structural noise of a suction unit's cover - Žumer, Jurij (Strojniški vestnik, 2008)
In this paper we report on a study of the vibrations of a suction unit's coverand the relation with the generated structural noise. The existing cover of the suction unit was designed, taking into account only the geometrical requirements. Two different methods were used for characterization of the vibration and structural noise of the cover: numerical modal analysis made with the FEM (Finite Element Method) and experimental modal analysis made during the operation of the suction unit. The results of the experimental modal analysis of the coverćs vibrations visually confirmed the results of a numerical modal analysis up to the 1st BPF (Blade Passing Frequency) and characterized the main exciting sources with the prevailing aerodynamic excitation. The vibration modal analysis tries to find a relation with the coverćs structural noise using an experimental local noise modal analysis. A different method of measurement of local structural noise is introduced.
Keywords: sesalne enote; pokrovi; vibracije; hrup; numerična analiza